The Optimality of Pure Competition in the Capacity Problem: Further Comment - Crew, Michael A. (Quarterly Journal of Economics, 1969)
Journal Article The Optimality of Pure Competition in the Capacity Problem: Further Comment Get access Michael A. Crew Michael A. Crew Carnegie-Mellon University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 83, Issue 2, May 1969, Pages 341–343, https://doi.org/10.2307/1883090 Published: 01 May 1969